(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Work-life balance does not include allocating the same amount of time to your personal and professional obligations, since this is quite unlikely to happen in reality. The balance between a person’s career and personal life will also change throughout time. The ideal balance will alter depending on your stage of life—from single to married to expecting children to close to retirement—so it is important to find it early on. You shouldn’t try to achieve a balance that is ideal or universally applicable. The two sides of a valid definition of work-life balance are, in reality, success and satisfaction. The following is a useful description of work-life balance: "Meaningful everyday success and satisfaction in each of my four life quadrants: work, family, friends, and self." By making sure that you not only succeed but also consistently demonstrate the pleasure of both your career and life, you may attain your ideal work-life balance. As a result of this study, it can be said that women in particular should prioritize striking a balance between their personal and professional lives. Unlike in the traditional economy, women today are expected to play a variety of roles that support both the growth of their families and their social contributions. To prevent conflicts that develop in their personal and professional lives, it is important for all women to pursue balanced lives. In creating a harmonious balance between their professional and family lives, women play a pivotal role. They cannot, under any circumstances, place the blame for their imbalance on others; if they do so, despair results, which inevitably has an impact on their health. So that work life is equalized, women must be empowered. The purpose of the research is to determine how work-life balance affects IT employees.